CASE STUDY OF THETICAL AND ANTITHETICAL ECONOMICS. TRANSITION OF ECONOMIC HEGEMONY - Kinoshita, Eizo (European Scientific Journal, ESJ, 2015)
The author discusses in this paper how economic hegemony of the world changed from time to time, as part of a case study of “Thetical and Antithetical Economics proposed by Eizo Kinoshita, Reference 1”. The author insists that a law like mechanism functions concerning the rise of a nation to the role of economic hegemon, which is summarized as “the collapse of a bubble economy in a country would help itself emerge as a new economic hegemon,” and verifies it from a historical point of view.